Performance enhancement of limestone calcined clay cement (LC3) using shale: industrial implementation Perspectives - Khuram Rashid; Mounir Ltifi; Idrees Zafar; Minkwan Ju (Engineering Science and Technology, an International Journal)
Limestone calcined clay cement (LC3) is one of prospective low-carbon ternary binders, developed by replacing 50 % of clinker with a combination of calcined clay (40 % kaolinite content) and limestone. However, for the optimization with low-grade clay, and their calcination temperatures remains a significant challenge for large-scale industrial production. This study investigates the potential enhancement of LC3 by incorporating shale/clay alternatives across three phases of casting. In the first phase, the mix proportions of the ternary components were varied to determine LC3 formulations ranging from LC3-10 to LC3-50, replacing ordinary Portland cement (OPC) with 10 % to 50 %, respectively. In the second phase, the optimized composition was further refined by increasing the calcination temperature of the shale/clay with 750, 800, and 850 °C. It was resulted that replacing OPC with up to 20 % LC3, combined with shale calcined at 800 °C, outperformed conventional cement in strength. The third phase focused on industrial plant implementation, where the shale-based LC3-15 and LC3-25 formulations were developed. The findings indicated that the LC3-15 and LC3-25 met the strength requirements of ASTM standards at all tested ages, with the LC3-15 also satisfying EN standards. An in-depth energy utilization analysis revealed significant environmental and economic benefits, with the LC3-25 production at an industrial scale, reducing CO2 emissions by 16.2 % and production costs by 11 %. It was demonstrated that the shale-based LC3-25 as a sustainable alternative to conventional cement.